2015
DOI: 10.1007/s10530-015-1045-6
|View full text |Cite
|
Sign up to set email alerts
|

Different dispersal histories of lineages of the earthworm Aporrectodea caliginosa (Lumbricidae, Annelida) in the Palearctic

Abstract: Earthworms are among the most abundant and ecologically important invasive species, and are therefore a good object for studying genetic processes in invasive populations. Aporrectodea caliginosa is one of the most widespread invasive earthworms in the temperate zone. It is believed to have dispersed from Europe to all continents except Antarctica. It is known that A. caliginosa consists of three genetic lineages, and genetic diversity is high both among and between them. We attempted to use that high genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 31 publications
0
19
0
5
Order By: Relevance
“…Although several complexes of cryptic species have been recently described in earthworms, highlighting the difficulties of morphological diagnosis in this taxon (King et al, 2008;Novo et al, 2010;Pérez-Losada et al, 2009;Shekhovtsov et al, 2016), there is not much data available in the literature on the genetic diversity within the P. corethrurus morphospecies (Cunha et al, 2014;Dupont et al, 2012). In three populations of P. corethrurus in the Azores archipelago, Cunha et al (2014) revealed the existence of two genetically divergent lineages which were morphologically indistinguishable.…”
Section: Evidence Of Cryptic Diversity?mentioning
confidence: 99%
“…Although several complexes of cryptic species have been recently described in earthworms, highlighting the difficulties of morphological diagnosis in this taxon (King et al, 2008;Novo et al, 2010;Pérez-Losada et al, 2009;Shekhovtsov et al, 2016), there is not much data available in the literature on the genetic diversity within the P. corethrurus morphospecies (Cunha et al, 2014;Dupont et al, 2012). In three populations of P. corethrurus in the Azores archipelago, Cunha et al (2014) revealed the existence of two genetically divergent lineages which were morphologically indistinguishable.…”
Section: Evidence Of Cryptic Diversity?mentioning
confidence: 99%
“…Здесь следует добавить, что наимень-шее генетическое разнообразие обычно отмечают у широ-ко распространенных космополитных видов, популяции которых обычно имеют малое число особей-основателей. Однако настолько низкого генетического раз нообразия не имеют даже филогенетические линии широко распро-страненных космополитных видов (например, Cameron et al, 2008;Fernández et al, 2011aFernández et al, , 2013Porco et al, 2013;Shekhovtsov et al, 2014aShekhovtsov et al, , 2016b. Это заставляет предпо-ложить, что линия 1 -космополитная, расселилась по территории Сибири и Дальнего Востока, по-видимому, в результате деятельности человека, и подтверждается тем, что собранные черви были приурочены к антропогенным местообитаниям: в Хакасии, Якутии и Магадане они най-дены на огородах, в Архаре -на заросшей лесом свалке, а на Камчатке -в роще, часто посещаемой людьми.…”
Section: Population Genetics Vavilov Journal Of Genetics and Breedingunclassified
“…Так, A. c. trapezoides и A. c. nocturna пигментированы, а A. c. caliginosa и A. c. tuberculata -нет; при этом нередко встречаются черви с промежуточной окраской (PérezLosada et al, 2009). Считается, что у представителей всех четырех подвидов поясок располага ется на одних и тех же сегментах, тем не менее зачастую можно обнаружить отклонения от диагноза (Shekhovtsov et al, 2016a). Различия между подвидами касаются также формы и положения пубертатных валиков, однако описа ны различные промежуточные варианты этих признаков (PérezLosada et al, 2009).…”
unclassified
“…Известно, что для комплекса A. caliginosa, как и для многих других видов дождевых червей, характерна вы сокая скрытая генетическая изменчивость (PérezLosada et al, 2009;Fernández et al, 2011aFernández et al, , 2012Fernández et al, , 2013Porco et al, 2013;Shekhovtsov et al, 2016a). M. PérezLosada с колле гами (2009) Известно, что для многих видов дождевых червей ха рактерно присутствие нескольких сильно дивергировав ших филогенетических линий, морфологические различия между которыми обычно не выражены.…”
unclassified
See 1 more Smart Citation